Hubungan Aktivitas Perawatan Diri Diabetes dengan Kontrol Glikemik Pasien Diabetes Mellitus Tipe 2 di Wilayah Kerja Puskesmas Padang Bulan Medan - Hutahaean, Moris Samsul Lamhot; Tarigan, Mula; Karota, Evi; Tanjung, Muhammad Sukri (Jurnal Ners, 2025)
Type 2 diabetes mellitus (T2DM) is a group of metabolic diseases that occur when the body cannot effectively use the insulin it produces, resulting in hyperglycemia. T2DM mostly affects adults and is usually caused by age, overweight and inactivity. To manage diabetes appropriately or achieve adequate glycemic control, patients must perform diabetes self-care activities by organizing a proper diet, doing physical exercise, monitoring blood sugar levels, complying with prescribed medications, performing foot care, and quitting smoking. The purpose of this study was to determine the relationship of diabetes self-care activities with glycemic control in type 2 diabetes patients in the Padang Bulan Medan Health Center. This research method is quantitative non-experimental with correlation design. The majority of respondents carried out insufficient self-care activities (47.1%) with 79.3% uncontrolled glycemic control. The relationship between diabetes self-care activities and glycemic control was significant with p = 0.000 (<0.001) with a value of r = 0.643. Health center workers are expected to provide diabetes self-care education. Improving the implementation of diabetes self-care activities is aimed at preventing further complications and improving the quality of life of patients. Keywords: Diabetes. T2DM, diabetes self-care activities, glycemic control